Deciding Desertion Cases in Absentia: Trials and Implications - Wibowo, Dava Prawira (Ius Poenale, 2023)
Military members are bound by strict laws and regulations, ensuring that all actions must align with the established legal frameworks. One of the most critical offenses within the Indonesian National Armed Forces (TNI) is desertion, given its significant impact on the integrity of the troops. This necessitates specific regulations for swift resolution and legal certainty. In cases where military personnel accused of desertion cannot be located, the judicial approach is particularly crucial. Employing a normative juridical method involves analyzing and interpreting legal principles and theoretical matters related to the crime, supported by an empirical juridical method that gathers insights from criminal law experts and law enforcement to reinforce the normative data. If the accused remains absent, the process to try the crime of desertion can proceed in absentia, according to Law No. 31 of 1997 concerning Military Justice, Article 143, which allows for a trial if the defendant does not appear by the time of the third summons. This provision ensures that proceedings can continue, upholding necessary discipline within the military. Judges deciding on cases of desertion consider three main aspects: juridical, based on formal statutory provisions; sociological, considering the social background of the defendant and the broader societal impact; and philosophical, focusing on ensuring that the punishment serves as a deterrent and upholds military discipline, aiming for a fair and just outcome. This comprehensive approach helps the military judicial system effectively address desertion, maintaining troop integrity and ensuring justice is served, even in the defendant's absence.